Pengaruh Persepsi Kualitas, Persepsi Value , Kepuasan Wisatawan, dan Kunjungan Ulang terhadap Rekomendasi Mulut Ke Mulut - Ali Hasan (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2012)
This research was designed to know the influence of quality perception, value perception, tourist satisfaction, and revisiting to Word of Mouth (WoM) recommendation. Methods that are used in this research are questioner to collect the data, part-whole used to test the validity and Cronbach alpha to test the reliability. Testing the normality, Linearity, multi colinearity, autocorrelation and heteroskedasticity is to detect the compatibility of using a model of the path regression as the test of hypothesis. The result of this research indicates that: (1) quality perception, value perception, tourist satisfaction, and revisiting significantly have positive effect positive to WoM recommendation, (2) quality perception has the positive influence to value perception, (3) quality perception has the positive influence which is very significant to tourist satisfaction, (4) quality perception has the positive influence which is significantly the revisiting, (5) quality preception has the positive influence which is significant to WoM recommendation, (6) perception assess has positive influence to tourist satisfaction, (7) perception assess is to own the positive influence which is significant to revisiting, (8) perception assess has the positve influence which is very to WoM recommendation, (9) tourist satisfavtion has a positive effect significantly to the revisiting, (10) tourist satisfaction has a positive effect to WoM recommendation, (11) resiviting has the positive influence which is very significant to WoM recommendation, and (12) revisiting has more dominant influence in creating WoM recommendation of Jogja tourism object to others people.